2019
DOI: 10.1021/acs.chemmater.9b04512
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Factor Control of Uniaxial Negative Thermal Expansion in a Layered Perovskite

Abstract: By tuning the tolerance factor, t, of the Ruddlesden-Popper oxide Ca 2 MnO 4 through isovalent substitutions, we show that the uniaxial coefficient of linear thermal expansion (CLTE) of these systems can be systematically changed through large negative to positive values. Highresolution X-ray diffraction measurements show that the magnitude of uniaxial negative thermal expansion (NTE) increases as t decreases across the stability window of the NTE phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
(81 reference statements)
0
11
2
Order By: Relevance
“…Several researchers have investigated the NIR-reflective, electrical, magnetic, and thermal expansion properties of Ca 2 MnO 4 . For example, the electrical properties of Ca 2 MnO 4 -based materials such as (Ca,RE) 2 MnO 4 (RE = Pr, Nd, Sm), Ca 2 (Mn,Nb)­O 4 , and Ca 2 MnO 4−δ have been reported. In addition, Ca 2 MnO 4 shows uniaxial negative thermal expansion by doping with Sr and Ti . The magnetic properties of (Ca,Sr) 2 MnO 4 have been investigated, and the corresponding solid solutions show antiferromagnetic interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated the NIR-reflective, electrical, magnetic, and thermal expansion properties of Ca 2 MnO 4 . For example, the electrical properties of Ca 2 MnO 4 -based materials such as (Ca,RE) 2 MnO 4 (RE = Pr, Nd, Sm), Ca 2 (Mn,Nb)­O 4 , and Ca 2 MnO 4−δ have been reported. In addition, Ca 2 MnO 4 shows uniaxial negative thermal expansion by doping with Sr and Ti . The magnetic properties of (Ca,Sr) 2 MnO 4 have been investigated, and the corresponding solid solutions show antiferromagnetic interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Trying to understand the origin of the peculiar thermal behavior of in-plane axes, we have looked at the few A n+1 B n O 3n+1 Ruddlesden–Popper (RP)-layered perovskites that show uniaxial NTE ( Ablitt et al., 2018 ),( Ablitt et al., 2017 ) Interestingly, in such oxidic compounds, NTE is seen to only occur along the layering axis and it is always associated with rotations of BO 6 octahedra about the layering axis, whereas no tilt about in-plane axes is present. In that regard, it should be indicated that in RP phases, because of their well-defined layering axis, it is customary to distinguish between rotations and tilts (see Figure S9 ) in that manner ( Ablitt et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, negative thermal expansion is both rarer and apparently more difficult to tune in inorganic framework materials, such as complex oxides [8][9][10]. The most common approach is chemical substitution, although it is generally challenging to change either the sign or the magnitude of the thermal expansion significantly in this way (recent work provides an impressive exception [11,12]). A significant barrier to designing effective strategies for highly tunable thermal expansion is that, with few exceptions, the microscopic factors controlling the temperature evolution of structural parameters are poorly understood.…”
Section: Introductionmentioning
confidence: 99%